2021
DOI: 10.1186/s12884-021-03914-2
|View full text |Cite
|
Sign up to set email alerts
|

A mixed-methods evaluation of hepatitis B knowledge, attitudes, and practices among migrant women in Thailand

Abstract: Background Globally 90 % of transmission of Hepatitis B virus (HBV) is from mother-to child and occurs predominantly in resource limited countries where the prevalence of HBV is high. Transmission could be interrupted by timely vaccinations but coverage remains problematic in these areas. Low knowledge or awareness of HBV may play a part in low vaccination coverage. This study examines the provision of antenatal care counselling with a focus on HBV in two different regions of northern Thailand,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 43 publications
0
11
3
1
Order By: Relevance
“…Furthermore, poor practices may play a vital role in low vaccination rates and increase exposure to the disease as well as their vulnerability to contracting and/or spreading the disease among potential people. 22 The present study findings suggest that more HB‐related health education, public awareness and promotion, and appropriate practice are required to eradicate HBV in Bangladesh. In terms of vaccination status, the current study showed that older participants (aged between 50 and above) received less HB vaccine.…”
Section: Discussionmentioning
confidence: 70%
“…Furthermore, poor practices may play a vital role in low vaccination rates and increase exposure to the disease as well as their vulnerability to contracting and/or spreading the disease among potential people. 22 The present study findings suggest that more HB‐related health education, public awareness and promotion, and appropriate practice are required to eradicate HBV in Bangladesh. In terms of vaccination status, the current study showed that older participants (aged between 50 and above) received less HB vaccine.…”
Section: Discussionmentioning
confidence: 70%
“…Between September 10, 2019 and March 30, 2019, 253 women were surveyed, 200 from SMRU and 53 from SH. Results of this survey have been previously documented in detail [ 23 ]. Briefly, age, number of children, and Hepatitis B positivity were not significantly different between the sites (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Willingness to vaccinate was previously reported to be unrelated to knowledge about hepatitis B [ 23 ]. In this dataset, there was no association between willingness to vaccinate and actual vaccine completion, which was not explored previously.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations